Legal Consequence on Certificate of Property Publishing By the National Land Agency for Unauthorized Purchase - Ari Setyo Aji; Umar Ma’ruf (Jurnal Akta, 2019)
The purpose of this study was to analyze: 1)To know and explain about factors which causes of invalidity of buying and selling land. 2) To determine the position of court cases 06 / Pdt.G / 2017 / PN.Btg and legal considerations the judges in deciding the case a quo. 3) To know and analyze the legal consequences of the issuance of certificates of property rights by the National pertananahan body over the unauthorized purchase has no legal force and is against the law in a civil case No.06 / Pdt.G / 20017 / PN.Btg, The approach method in this research is the socio-juridical. The data used are primary and secondary data obtained through interviews and literature, while the data analysis conducted Qualitative AnalysisResults of the research can be concluded: 1) that the sale and purchase of land especially to land inheritance, should involve and seek approval to all heirs. 2) that the sale and purchase of land inheritance that does not involve all the heirs then selling the land becomes invalid so that Mutatis Mutandis certificate publishing rights Illegitimate and Cancel by the Law. 1) that also challenged that the plaintiff must file a lawsuit prior to the Parties involved in the process of buying and selling land inheritance, from the Seller, Buyer, PPAT, and the Land Office as a party to issue a Certificate of Rights Reserved. The solution that should PPAT and Land Office to socialize, it aims to provide insight to the public especially to the sale and purchase of land.Keywords: Legal Consequence; Certificate; Property ;ublishing; Unauthorized Purchase.